Development of a Reaction Light Tool for Smash Targets in Volleyball - Khairul Fahmi Fadhlani; Sanusi Hasibuan; Ibrahim Sembiring; Indra Kasih (RIRAI Publisher, 2022)
This type of research is development (research and development). In research on the development of volleyball smash tools. In this study the authors carried out 8 research steps due to the limitations of the researchers. This research is planned to be carried out in September 2022. The research location was carried out at the Nusantara Private High School extracurricular club. In this study, a small trial was given to 10 volleyball extracurricular athletes from Nusantara Private High School, and a large trial was conducted to 20 volleyball extracurricular athletes from Nusantara Private High School. Based on the description of the research results and discussion, the conclusions in this study were determined, namely the results of a large group tryout by 20 athlete respondents from SMA Nusantara Lubuk Pakam. Where the score obtained in the large group trial was 1270 with a percentage of 90.71. The results of the large group tryout by trainer respondents were 2 people from Lubuk Pakam Nusantara High School. Where the results in the large group trial were 104 with a category of 94.54%, meaning that the large group trial of product responses was very feasible. The result of the final revision of the volleyball expert by obtaining a score of 100 with a percentage of 90.91% means that the product development of this smash tool is very feasible. Then the media experts obtained a score of 62 with a percentage of 95.38% meaning that the product development of this smash tool is very feasible.